Pemanfaatan Teknologi Geospatial Intelligence (GEOINT) untuk Peningkatan Keamanan dan Pengelolaan Maritim di Indonesia - Yeri Kusmantoro; Trismadi Trismadi; Gentio Harsono (Departement of Mathematics Education, 2024)
Indonesia, as the largest archipelagic country in the world, faces significant challenges in maintaining maritime security and managing its marine resources. In this context, Geospatial Intelligence (GEOINT) has emerged as an important tool that can support maritime security strategies and management effectively. This study uses a literature study method to explore the role of GEOINT in supporting Indonesia's national security. The analysis was conducted by reviewing various literatures that discuss the application of GEOINT in maritime security, traffic surveillance, natural resource management, and emergency responsse to disasters. The results of the study indicate that GEOINT plays a crucial role in improving maritime surveillance through the use of satellite imagery, space sensors, and predictive analytics. This technology also supports maritime traffic management, marine resource conservation, and recovery after maritime disasters. However, the implementation of GEOINT in Indonesia still faces several challenges, including limited technological infrastructure and inter-agency coordination. The conclusion of this study emphasizes the importance of investing in GEOINT technology and increasing human resource capacity to maximize the potential of GEOINT in supporting Indonesia's maritime security. International collaboration and the development of supportive policies are also needed to overcome existing challenges and ensure the success of GEOINT implementation in Indonesia.